The analysis of a computer music network and the implementation of essential subsystems - Wilks, Antony John (Rhodes University, Faculty of Science, Department of Computer Science, 1995)
The inability to share resources in commercial and institutional computer music studios results in non-optimal resource utilisation. The use of computers to process, store and communicate data can be extended within these studios, to provide the capability of sharing resources amongst their users. This thesis describes a computer music network which was designed for this purpose. Certain devices had to be custom built for the implementation of the network. The thesis discusses the design and construction of these devices.
Keywords: Computer networks; Computer music; MIDI (Standard)